Implementasi Metode Inkuiri Terbimbing untuk Meningkatkan Kemampuan Mengenal Pola dan Berpikir Kritis pada Anak TK B Sekolah Cikal, Jakarta [Implementation of Guided Inquiry Method to Increase Ability in Recognizing Pattern and Critical Thinking in TK B Sekolah Cikal, Jakarta Children] - Saraswati, Kathie (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
The study of the students in Kindergarten B Cikal School, Jakarta is based on the weaknesses of students capability in recognizing complex pattern and in order to fostering children’s critical thinking. Based on the problem stated, a solution that will be given was through guided inquiry method. The purpose of this research is to describe children’s ability in recognizing pattern and in fostering critical thinking through guided inquiry method for Kindergarten B children in Cikal School, Jakarta. This research used Classroom Action Research (action research class) is designed in three form of a repeating cycles. Each cycle comprises four phases: planning, action, observation and reflection. The subjects in this study were 6 children from the total of 20 children, that consisted of 3 boys and 3 girls in Kindergarten B Cikal School Jakarta. Collecting data technique that used was qualitative descriptive. Thus, the conclusion is that by using a quided inquiry method can increase the ability of recognizing pattern also fostering children in critical thinking in Kindergaten B Sekolah Cikal, Jakarta.